2016
DOI: 10.7863/ultra.15.02043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low‐Intensity Pulsed Ultrasound on Distraction Osteogenesis Treatment Time

Abstract: Current available evidence suggests that low-intensity pulsed US therapy may provide a reduction in the overall treatment time for tibial distraction osteogenesis. However, this conclusion should be considered with caution, given the moderate to high risk of bias in the included randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…The positive effect of LIPUS on acceleration of bone regeneration in this systematic review are consistent with the results of a previous review on five human trials (four on tibia and one on a mandible) studying the effect of LIPUS during DO [40]. This review studied the optimal time for LIPUS applications, the appropriate intensity of LIPUS and the histological aspects including the ossification pattern, which could serve as a milestone for future studies investigating the biological mechanism of LIPUS on bone regeneration.…”
Section: Discussionsupporting
confidence: 86%
“…The positive effect of LIPUS on acceleration of bone regeneration in this systematic review are consistent with the results of a previous review on five human trials (four on tibia and one on a mandible) studying the effect of LIPUS during DO [40]. This review studied the optimal time for LIPUS applications, the appropriate intensity of LIPUS and the histological aspects including the ossification pattern, which could serve as a milestone for future studies investigating the biological mechanism of LIPUS on bone regeneration.…”
Section: Discussionsupporting
confidence: 86%
“…Clinically, LIPUS was reported to accelerate bone maturation in DO, and reduce the overall time to removal of the fixation device in clinical trials [71] , [72] , [73] : El-Mowafi et al [71] indicated that the mean healing index in the ultrasound group was 30 (27–36) d/cm, as compared with the control group with 48 (42–75) d/cm in a 20-patient trial [71] ; Salem et al [72] reported 27% faster callus maturation and 33% more radiographic callus density in the LIPUS group in a 21-patient trial; Dudda et al [73] showed that the fixation gestation period was decreased for 43.6 days in the ultrasound group with no negative effects in a 36-patient trial. A meta-analysis report [20] , [74] concluded that LIPUS was an effective treatment to reduce the overall treatment time for DO, yet the lines of evidence were weak; thus, large-scale clinical studies are needed to confirm its efficacy.…”
Section: Distraction Osteogenesismentioning
confidence: 99%
“…6 7 8 9 10 11 12 13 14 Our systematic review, however, differs from previous systematic reviews in several important aspects. Firstly, we include the recently published TRUST trial,16 by far the largest trial on LIPUS treatment for bone healing, which reported a number of outcomes important to patients.…”
Section: Discussionmentioning
confidence: 80%
“…6 7 8 9 10 11 12 13 14 Because existing randomized controlled trials were limited by small sample size, risk of bias, inconsistent results, and failure to cover outcomes important to patients, no review offered definitive conclusions. All reviews identified the need for additional randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%